2017
DOI: 10.17706/ijbbb.2017.7.2.110-117
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Polymeric Spinal Cages Using Ct Based Finite Element Method

Abstract: Abstract:Interbody fusion devices are gaining acceptance as a treatment method of mainly for disc degeneration diseases and other medical conditions. Posterior lumbar interbody fusion (PLIF) cage is used in the procedure to maintain stability and promote fusion between vertebrae. Poly lactic acid (PLA) is assumed to be the alternative material which could provide cheaper material and lower production cost. However, these implants often cause subsidence failure at the endplate, resulting in injury risk and mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, none of these outcomes account for bone failure which is the actual cause of Contrary to other studies which found more inelastic strains in extension or lateral bending, in our model plastic 299 strains were more prone to occur in the anterior part of the caudal vertebra during flexion. This difference may 300 be related to the use of posterior fixation by Jalil et al [35] which restricted the flexion motion decreasing the 301 compressive force on the anterior part of the endplates. Regarding the cage parameters, the inelastic strains 302 increased for cages with: high radius, high curvature and an anterior position.…”
mentioning
confidence: 99%
“…However, none of these outcomes account for bone failure which is the actual cause of Contrary to other studies which found more inelastic strains in extension or lateral bending, in our model plastic 299 strains were more prone to occur in the anterior part of the caudal vertebra during flexion. This difference may 300 be related to the use of posterior fixation by Jalil et al [35] which restricted the flexion motion decreasing the 301 compressive force on the anterior part of the endplates. Regarding the cage parameters, the inelastic strains 302 increased for cages with: high radius, high curvature and an anterior position.…”
mentioning
confidence: 99%
“…No cases were localized in the posterior portion, even in the dual cage group. Prior finite element analyses showed stress distribution in interbody cages included axial load stress on interbody cages were concentrated anteriorly [30][31][32][33][34][35] In addition, a cadaveric study by Sengupta et al 36 further demonstrated anterior localization of cage stress. This eccentric distribution might be derived from the stress-shielding effect of the high stiffness of PS-rod fixation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the application of PI could significantly reduce the cage-endplate interface stress by 50 to 60% if compared to non-instrumented cage [1]. In addition, the application of PI would also mitigate the risks of cage failure and cage migration by increasing the cage pullout resistance [9][10] [18]. Even though it seems like the increased stress on the pedicle screw would increase the load burden on that area, however we have to bear in mind that the stress generation by the PEEK-based cage was comparably lower than the stress generation produced by titanium-based cage construct.…”
Section: Discussionmentioning
confidence: 99%